2010
DOI: 10.1111/j.1745-4530.2009.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Foam‐mat Freeze‐drying of Apple Juice Part 2: Stability of Dry Products During Storage

Abstract: Sorption isotherms at 5, 20 and 35C and glass transition temperature as a function of water content were evaluated for foamed (3% egg white and 1% methylcellulose) and nonfoamed freeze‐dried apple juice by using the static gravimetric method and differential scanning calorimetry, respectively. Equilibrium isotherms were fitted to the Guggenheim–Anderson–de Boer equation, whereas glass transition temperature to the Gordon–Taylor model. After freeze‐drying at 20C during 48 h, the dry products were stored at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…Moisture contents after 56 d storage of different sample materials were not different at the 5% level, however differences between average initial (day 0) and final (day 56) moisture contents were significant. RMC at 56 d of storage was slightly higher in foamed protective agents than in nonfoamed ones possibly due to increased surface area of foamed protective agents, a result which is in agreement with Raharitsifa and others () who reported that foamed freeze‐dried apple juice samples were more hygroscopic than nonfoamed ones. Despite an important increase in sample humidity during storage, glass transition temperatures just decreased up to 7.5% from the initial average value of 67.25 °C (Table ), remaining above 60 °C during storage.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moisture contents after 56 d storage of different sample materials were not different at the 5% level, however differences between average initial (day 0) and final (day 56) moisture contents were significant. RMC at 56 d of storage was slightly higher in foamed protective agents than in nonfoamed ones possibly due to increased surface area of foamed protective agents, a result which is in agreement with Raharitsifa and others () who reported that foamed freeze‐dried apple juice samples were more hygroscopic than nonfoamed ones. Despite an important increase in sample humidity during storage, glass transition temperatures just decreased up to 7.5% from the initial average value of 67.25 °C (Table ), remaining above 60 °C during storage.…”
Section: Resultssupporting
confidence: 90%
“…This fact could be explained because of the increased surface area of foamed protective agents and consequently, the higher exposure of B. longum RO175 to oxygen and moisture during storage. Raharitsifa and others () found that foamed freeze‐dried apple juice was more stable during storage than nonfoamed one. In their case, however, composition of foamed and nonfoamed materials was different causing significant differences in glass transition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Sorption isotherms characterize a relationship between water content and its activity at constant temperature (Sablani et al, 2007) and have been widely conduced on edible films (Shih et al, 2011). Selection of an appropriate mathematical model of sorption behaviour is a difficult task, because of complex chemical composition and structure of food (Raharitsifa and Ratti, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sorption behavior of various foods and the influence of temperature on the relationship between equilibrium moisture content and water activity were studied and modeled extensively in recent years (McMinn et al . ; Raharitsifa and Ratti ; Sopade et al . ; Cladera‐Olivera et al .…”
Section: Introductionmentioning
confidence: 99%